March 19, 2014

1,492 views
1,344 views

Published on

0 Comments
0 Likes
Statistics
Notes
  • Be the first to comment

  • Be the first to like this

No Downloads
Views
Total views
1,492
On SlideShare
0
From Embeds
0
Number of Embeds
829
Actions
Shares
0
Downloads
3
Comments
0
Likes
0
Embeds 0
No embeds

No notes for slide

March 19, 2014

  1. 1. Polynomials Factoring Today: 1. Factor by GCF 2. Factor by Grouping
  2. 2. Factors  Factors (either numbers or polynomials) – When an integer is written as a product of integers, each of the original integers in the product is a factor of the final number. – When a polynomial is written as a product of polynomials, each of the original polynomials in the product is a factor of the final polynomial. Factoring – reducing a polynomial to its simplest form Greatest Common Factor  The largest quantity that is a factor of all the integers or polynomials involved. Finding the GCF of a List of Integers or Terms 1) Prime factor the numbers. 2) Identify common prime factors. 3) Take the product of all common prime factors. 4) If there are no common prime factors, GCF is 1.
  3. 3.  Find the GCF of each list of numbers Example 1) 12 and 8 12 = 2 · 2 · 3 8 = 2 · 2 · 2 So the GCF is 2 · 2 = 4. 2) 7 and 20 7 = 1 · 7 20 = 2 · 2 · 5 There are no common prime factors so the GCF is 1. 3. 144, 256 and 300 144 = 2 · 2 · 2 · 3 · 3 256 = 2 · 2 · 2 · 2 · 2 · 2 · 2 · 2 300 = 2 · 2 · 3 · 5 · 5 So the GCF is 2 · 2 = 4.
  4. 4. Example Find the GCF of each list of terms. 6x5 and 4x3 6x5 = 2 · 3 · x · x · x · x · x 4x3 = 2 · 2 · x · x · x So the GCF is 2 · x · x · x = 2x3 a3b2, a2b5 and a4b7 a3b2 = a · a · a · b · b a2b5 = a · a · b · b · b · b · b a4b7 = a · a · a · a · b · b · b · b · b · b · b So the GCF is a · a · b · b = a2b2
  5. 5. Factoring Polynomials (Factoring out the GCF) - The first step in factoring a polynomial is to find the GCF of all its terms. - Then we write the polynomial as a product by factoring out the GCF from all the terms. - The remaining factors will form a polynomial. Example Factor out the GCF in each of the following polynomials. 1) 6x3 – 9x2 + 12x = 3 · x · 2 · x2 – 3 · x · 3 · x + 3 · x · 4 = 3x(2x2 – 3x + 4) 2) 14x3y + 7x2y – 7xy = 7 · x · y · 2 · x2 + 7 · x · y · x – 7 · x · y · 1 = 7xy(2x2 + x – 1)
  6. 6. Example Factor out the GCF in each of the following polynomials. 1) 16x4 + 8x2 + 12x3 = 4 · x2 · 2 · 2 · x2 + 4 · x · x · 2 + 3 · x2 · x .4 = 4x2 (4x2 – 2 + 3x) 2) 21x3y + 14x2y – 7xy = 7 · x · y · 3 · x2 + 7 · x · y · 2 · x – 7 · x · y · 1 = 7xy(3x2 + 2x – 1)
  7. 7. Factoring by Grouping Factoring polynomials often involves additional techniques after initially factoring out the GCF. One technique is factoring by grouping. Factor xy + y + 2x + 2 by grouping. Notice that, although 1 is the GCF for all four terms of the polynomial, the first 2 terms have a GCF of y and the last 2 terms have a GCF of 2. xy + y + 2x + 2 = x · y + 1 · y + 2 · x + 2 · 1 = y(x + 1) + 2(x + 1) = (x + 1)(y + 2) Example
  8. 8. Factoring a Four-Term Polynomial by Grouping 1) Arrange the terms so that the first two terms have a common factor and the last two terms have a common factor. 2) For each pair of terms, use the distributive property to factor out the pair’s greatest common factor. 3) If there is now a common binomial factor, factor it out. 4) If there is no common binomial factor in step 3, begin again, rearranging the terms differently. If no rearrangement leads to a common binomial factor, the polynomial cannot be factored. Examples 1) x3 + 4x + x2 + 4 = x(x2 + 4) + 1(x2 + 4) = (x2 + 4)(x + 1) 2) 6ax + by + 2bx + 3ay
  9. 9. Remember that factoring out the GCF from the terms of a polynomial should always be the first step in factoring a polynomial. This will usually be followed by additional steps in the process. Factor 90 + 15y2 – 18x – 3xy2. = 3(5 · 6 + 5 · y2 – 6 · x – x · y2) = 3(5(6 + y2) – x (6 + y2)) = 3(6 + y2)(5 – x) Example Combining Factoring Methods
  10. 10. Class work

×